Live at Mister Kelly's [videorecording (DVD)] - Kurtis, Bill (Virgil Films, 2021)
The iconic Mister Kelly's illuminated legendary Chicago's Rush Street, and the entire country, by launching talents like Barbra Streisand, Richard Pryor, Bob Newhart, Bette Midler, and Steve Martin. It's visionary owners George and Oscar Marienthal smashed color and gender barriers to put unknown, controversial voices on stage and transform entertainment. Now, with the club long gone, and its star talent reaching its golden years, George's son David and director/screenwriter Theodore Bogosian go on a quest to collect the memories of the clubs before they are lost. Includes interviews with Bob Newhart, the Smothers Brothers, Dick Gregory, Lainie Kazan, Herbie Hancock, Dick Cavett, Tim Reid, Fred Willard, and Ramsey Lewis. How do you change the world with a laugh and a song? Find out in a film that documents the rise and fall of one of American entertainment's great proving grounds.